Spatial Analysis of the Degraded Forest Areas in Idmine Forest-Morocco Using Geoscience Capabilities - LAARIBYA, Said; ALAOUI, Assmaa; AYAN, Sezgin; BENABOU, Abdelkader (Kastamonu University, 2021)
Aim of study: The aim of the study is to present a diagnosis for the state of Argan forest degradation in Morocco through GIS and remote sensing utilizing Sentinel 2 satellite images of the year 2019 (dated 28/08/2019). Area of study: The study was carried out in a forest commune in Idmine, South West Morocco, which is located in semi-arid bioclimatic region. Material and methods: In the study, two methods were tested. These are; (i) the vegetation indices (VIs) [Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Soil-Adjusted Vegetation Index (SAVI), Brilliance Index (IB)] and their combination and (ii) the supervised classification and spectral analysis. Main results: Two methods have given the same results (Kappa coefficient=90%) to describe the state of forest degradation. Consequently, three classes pertaining to forest degradation within the study area were; low (34%), medium (44%) and critical degradation (22%). Highlights: This monitoring might help managers to create forest management plans and to evaluate the speed of deforestation and degradation.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land